2011
DOI: 10.1002/ange.201101013
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Hydrogen Bonding Between a Clicked C3‐Symmetric Triazole Derivative and Carboxylic Acids for Columnar Liquid‐Crystalline Assemblies

Abstract: Perfekt ergänzt: Eine Reihe discotischer H‐Brücken‐gebundener Komplexe wurde aus einem durch Klick‐Chemie hergestellten Triazolderivat mit C3‐Symmetrie und Carbonsäuren erhalten (siehe Bild; R1, R2=Alkylgruppen). Wegen ihrer ausgedehnten starren Kernstruktur konnten die supramolekularen Scheiben unter Bildung hexagonaler columnarer flüssigkristalliner Phasen aufeinander gestapelt werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Benzoic acids received considerable attention as external structure directing agents, 8 supramolecular clips, 9 complementary H-bonded mesogenic discs, 10 molecular templates, 11,12 and model amphiphilic systems for Langmuir−Blodgett film fabrication. 13−15 They are known to crystallize as cyclic dimers when no other competing hydrogen bonds are present.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzoic acids received considerable attention as external structure directing agents, 8 supramolecular clips, 9 complementary H-bonded mesogenic discs, 10 molecular templates, 11,12 and model amphiphilic systems for Langmuir−Blodgett film fabrication. 13−15 They are known to crystallize as cyclic dimers when no other competing hydrogen bonds are present.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Benzoic acids received considerable attention as external structure directing agents, supramolecular clips, complementary H-bonded mesogenic discs, molecular templates, , and model amphiphilic systems for Langmuir–Blodgett film fabrication. They are known to crystallize as cyclic dimers when no other competing hydrogen bonds are present. Although the catemeric motif is generally seen in carboxylic acids like formic acid, acetic acid, β-tetrolic acid, oxalic acid, and fumaric acid, it is reported that the dimer motif in benzoic acids is unfavorable compared to catemeric when bulky substituents are present …”
Section: Introductionmentioning
confidence: 99%
“…On cooling from the isotropic liquid phase, the LC phase at 181 °C displayed a fan‐like texture, which is typically found in the columnar LC phase of discotic LCs (Figure 1 b). 17 On further cooling to the other LC phase at 159 °C, the fan‐like texture did not alter, instead persisting to room temperature (Figure 1 c). Only the texture color changed, which is due to some variations in the sample thickness as the temperature decreased.…”
mentioning
confidence: 96%
“…In a subsequent publication, the same group prepared another series of C 3 -symmetric triazole compounds (113 a-c) from 1,3,5-tris(alkyl-1-H-1,2,3-triazol-4-yl)benzene (TTB) following a similar synthetic route. [107] The reaction of the triazole compounds with trioctyloxy benzoic acid (1:3 molar ratio) lead to the formation of supramolecular complexes 114 a-c through hydrogen-bonding interactions (Scheme 36). Hydrogen bonds are formed by one nitrogen atom of each triazole ring with the hydroxyl hydrogen of the carboxylic acid groups.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%